Investigación de mercado para evaluar el impacto socio-económico originado por el incremento de las operaciones del aeropuerto internacional Cotopaxi, en el sector hotelero de la ciudad de Latacunga - Vilca Llano, Darwin Patricio (2015)
This present research has as purpose evaluated the socio-economic caused by the increase of the Cotopaxi International Airport operation; the hospitality of Latacunga oriented. This work was divided in three chapters, which has helped to have an adequate theoretical foundation and a descriptive system of a sequential and orderly manner that served as a reference in order to develop market research.